Corymine Potentiates NMDA-Induced Currents in Xenopus Oocytes Expressing NR1a/NR2B Glutamate Receptors - Pathama Leewanich; Michihisa Tohda; Hiromitsu Takayama; Samaisukh Sophasan; Hiroshi Watanabe; Kinzo Matsumoto (Elsevier, 2005)
Previous studies demonstrated that corymine, an indole alkaloid isolated from the leaves of Hunter zeylanica, dose-dependently inhibited strychnine-sensitive glycine-induced currents. However, it is unclear whether this alkaloid can modulate the function of the N-methyl-D-aspartate (NMDA) receptor on which glycine acts as a co-agonist via strychnine-insensitive glycine binding sites. This study aimed to evaluate the effects of corymine on NR1a/NR2B NMDA receptors expressed in Xenopus oocytes using the two-electrode voltage clamp technique. Corymine significantly potentitated the NMDA-induced currents recorded from oocytes on days 3 and 4 after cRNA injection but it showed no effect when the current was recorded on days 5 and 6. The potentiating effect of corymine on NMDA-induced currents was induced in the presence of a low concentration of glycine (≤0.1 µM). Spermine significantly enhanced the potentiating effect of corymine observed in the oocytes on days 3 and 4, while the NMDA-receptor antagonist 2-amino-5-phosphonopentanone (AP5) and the NMDA-channel blocker 5-methyl-10,11-dihydro-5H-dibenzo[a,d]cyclohepten-5,10-imine (MK-801) reversed the effect of corymine. On the other hand, the nonspecific chloride channel blocker 4,4-di-isothiocyano stilbene-2,2-disulfonoc acid (DIDS) had no effect on the corymine potentiation of NMDA currents. There was no good correlation between corymine- and spermine-induced potentiation of the NMDA-current response in Xenopus oocytes. These results suggest that corymine potentiates the NMDA-induced currents by interacting with a site different from the spermine binding site. Keywords:: corymine, potentiating effect, NR1a/NR2B NMDA receptor, Xenopus oocyte